Tarsila do Amaral: seu legado como objeto de memória e consumo (1995-2015) - Roxane Sidney Resende de Mendonca (2016)
This thesis proposes a study of the interrelations between art, memory and consumption that have intensified in the twenty-first century, and resorts to cultural history as a research tool. Reappropriations of the legacy of Tarsila do Amaral (1886- 1973) in commercial products, produced between 1995 and 2015, are taken as research objects. Our aim was to investigate how these products acted on the construction of the painter's image as we know it in the present. Interest in this studyarose from the realization that there is today an expansion movement of the artist's legacy beyond the artistic field, in several productions of the cultural industries, from the sale of the painting Abaporu (1928), in 1995. Through the lenses of cultural history, and taking into account Chartier (2002a, 2002b) and Certeau (2005, 1998), we consider the reappropriations as cultural practices and representations that establish connections between the time of Tarsila, highlighted the 1920s, and thetime of the products, between 1995 and 2015, moment in which aesthetic values and memories related to the arts are used as tools to make consumption more pleasurable and products more attractive. As documentary references of the 'time of Tarsila', books, exhibition catalogs, newspapers and the artistic production of the painter were taken into account. The 'time of the product' was investigated throughwebsites, blogs, newspapers, magazines, exhibition catalogs, commercial goods and other cultural productions that have enabled us to understand the current interest in the life and work of Tarsila. We have realized, through the analysis of commercial products, that the reappropriations of Tarsila's legacy are practices and cultural representations in the context of hybrid cultures and of transaesthetic artistic capitalism, articulating and selecting elements of the past that connect with elements from the present, a process called 'policy of memory'. We have concluded that commercial products are, along with other cultural productions, networks of heterogeneous elements, or devices, that overlap interests in different times and spaces and act in a complementary manner on the construction of Tarsila do Amaral's memory of the XXI century.